Em busca da integridade no SUS: conhecendo a integração da atenção básica à rede assistencial por meio da teoria de resposta ao item - Lenir Aparecida Chaves (2015)
INTRODUCTION: The National Policy of Basic Attention (2011) define Family Health as a strategy for basic attention consolidation and the Attention Nets as reference to the organization of an integral care. Evidences suggests that are of vital importance the actions ofregionalization, matricial care, communication, information, regulation and shared management for the network planning. However, problems related to the difficulty in access to the other levels of complexity in the system are a great challenge to the consolidation of SUS. OBJECTIVE: Evaluate the integration of the Basic Attention to the SUS attentionnetwork, using data from PMAQ-AB, Brazil, 2012. METHODS: Transversal study, based on the data from 17.202 family Health teams that answered to the external evaluation from the Program for Access and Quality Improvement in Primary Care/PMAQ-AB. To measure the teams' integration abilities to the assistencial network the Item Response Theory was used through the gradual response model Samejima (GRM). To estimate the integration level was used the abilities scale (-3 to 3) to the questions selected on module II (Interview with a team professional). Posteriorly, defined the gaps to classify the teams: low, medium and hight integration. The score were interpreted using the word cloud visualization technique that allowed us to get which one is the response category of the most common item in different levels of integration defined in the study . Then, was possible to verify their impact on theteams' performance and identify their behaviour. RESULTS: From the items used on the study, 12 had great discrimination betwin the teams on PMAQ, because they carry a greater level of information about their integration to the network. From them, are highlighted the ones refered to matricial support actions: medical appointment; case discussions; shared clinical actions; joined construction of therapeutic projects; permanent education activities; territorial interventions and visits with AB professionals that had their best performance in the level classified as medium integration and, despite hight abilitie is not demanded from theteams, have the highter values correlated with the final grade (>500). However, the item "discussion process work" requires high ability of the teams. Besides that, the items: Has communication channel/Has NASF support/Always - sometimes specialists contact AB/Frequency of weekly, biweekly and monthly support/Has contact list with AB/Receives CAPS support/Has 1 or 2 marking centrals/Sometimes - contact AB with specialists/There are from 1 to 3 communication fluxes/Has 3 marking centrals/Always - contact AB with specialists and There are and There are > 4 communication fluxes" has its best response category localized on the hight integration level, when we use the word cloud visualizationtechnique. CONCLUSION: The realization of the matricial support actions evaluated on PMAQ-AB improved the performance of the family health teams. In the same way, but in a smaller degree, the items referred to communication reinforce this understanding. However, despite the achievements in the country's health policy, the frequency around (50%) from the worse for the items of the study, highlights the necessity for qualification of the integration between the actions of Specialized Attention and basic attention to the consolidation of an embracing Health Primary Attention.